PENERAPAN STRATEGI ACTIVE LEARNING TIPE QUIZ TEAM UNTUK MENUMBUHKAN KARAKTER RASA INGIN TAHU SISWA DALAM PEMBELAJARAN SEJARAH (Penelitian Siklus Kelas: X MIIA 3 SMA Kartika XIX-1 Bandung) - Suhaibah Aslamiyah; Erlina Wiyanarti (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2017)
This research aims to increasing the student’s curiousity character in learning history. Through the observation, it can be noticeable that curiousity character in X MIIA 3 is on minimum level. The curiousity character can be seen by the level of student’s initiative or interest toward the process of learning history, such as in asking question, answering the question, or student’s capability to contribute on learning activity. This research used Classroom Action Research (CAR) by using design research that invented by Kemmis and Mc.Taggart which realized by four cycles. The researcher use many technique of collecting data such as observation, interview, and study documentation. This research also used the research instrument such as observation instrument, interview instrument, and field data. Based on the final result can be revealed that Active Learning Tipe Quize Team strategy can increase the student’s curiosity character in X MIIA 3. The development of curiosity increased in every cycle and it can be countable by the average of value in every single cycle. Based on the data, it can be described that in action I, the average of value is (58.53%). In action II, the achievement is (71.42 %). Then in action III, the data average got (71.42 %). And in action IV, the data average is (71.03%). all of data shows that student’s curious character in X MIIA 3 SMA Kartika XIX-1 Bandung increased after the researcher applied the active learning tipe quiz team strategy in history class.